The lives and afterlives of the library of the Maronite physician Ḥannā al-Ṭabīb (c. 1702–1775) from Aleppo - Krimsti, F (Brill Academic Publishers, 2018)
In eighteenth-century Aleppo, books acquired an unprecedented significance among Aleppo’s Christians, against the background of an expanding “culture of the book”. This paper attempts to reconstruct the library of the Maronite physician Ḥannā al-Ṭabīb (c. 1702–1775), based on ownership statements in manuscripts purchased by the German scholar and Oriental traveller Ulrich Jasper Seetzen (1767–1811) in Aleppo, presently preserved in Gotha’s Research Library. Proceeding from an assessment of the ownership statements and a thematic analysis of the library, the paper will address the implications for our understanding of book ownership in the social and intellectual milieu of the owner. It will be argued that owning books was a facet of an intensifying and active – not passive – preoccupation with literature among Christians.